An Assessment of Service Quality and Airport Elements Influential to Travellers’ Experience at Ilorin International Airport - O.J, Adediran (Journal of Tourism Management Research, 2020)
The level of acceptability of a traveller’s experience is important in determining the perceived value of airport service quality. To examine the level of the quality of service travellers’ experienced from airport elements and to identify airport elements that are influential in this regard, this quantitative study was conducted. With a structured questionnaire that was administered to 413 non-randomly selected participants, a total of 398 valid responses was received and analyzed using frequency, t-test, factor analysis and Analysis of Variance (ANOVA). Findings show that, in general, travellers’ assessment of the quality of service experienced at Ilorin International Airport was not impressive. The result of the factor analysis used in identifying the service elements that are influential also shows that eight of the thirty-five variables are influential to travellers’ experience. Finally, the results of the five null hypotheses tested at 0.05 level of significant show that travellers’ demographic characteristics do not influence their response. The study recommended that a national minimum standard with regards to infrastructural availability, adequacy and maintenance should be developed while Kwara State government should invest in infrastructure development and maintenance at the airport. Finally, the airport management has been enjoined to periodically collect travellers’ feedback on service experience and suggestions on the area to be improved upon for quality service experience identified.